Continuous‐Flow Amide and Ester Reductions Using Neat Borane Dimethylsulfide Complex. Issue 7 (20th February 2020) - Ötvös, Sándor B.; Kappe, C. Oliver
Abstract: Reductions of amides and esters are of critical importance in synthetic chemistry, and there are numerous protocols for executing these transformations employing traditional batch conditions. Notably, strategies based on flow chemistry, especially for amide reductions, are much less explored. Herein, a simple process was developed in which neat borane dimethylsulfide complex (BH3 ⋅DMS) was used to reduce various esters and amides under continuous‐flow conditions. Taking advantage of the solvent‐free nature of the commercially available borane reagent, high substrate concentrations were realized, allowing outstanding productivity and a significant reduction in E‐factors. In addition, with carefully optimized short residence times, the corresponding alcohols and amines were obtained in high selectivity and high yields. The synthetic utility of the inexpensive and easily implemented flow protocol was further corroborated by multigram‐scale syntheses of pharmaceutically relevant products. Owing to its beneficial features, including low solvent and reducing agent consumption, high selectivity, simplicity, and inherent scalability, the present process demonstrates fewer environmental concerns than most typical batch reductions using metal hydrides as reducing agents. Abstract : Go with the flow : Neat borane dimethylsulfide is used to reduce various esters and amides under continuous‐flow conditions in a simple yet efficient process. The application of the neat reducing agent in combination with highly concentrated substrate solutions at short residence times enables highly productive reductions with fewer environmental concerns than classical metal‐hydride‐mediated batch reductions.